Flecha al sol : un cuento de los indios Pueblo - McDermott, Gerald (New York : Puffin Books, 1991)
An adaptation of the Pueblo Indian myth which explains how the spirit of the Lord of the Sun was brought to the world of men.
Translation of: Arrow to the sun.
Keywords: Pueblo Indians -- Folklore; Pueblo Indians -- Folklore -- Juvenile fiction; Indians of North America -- Folklore -- Juvenile fiction